2019
DOI: 10.1021/acssuschemeng.8b05935
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Self-Standing and Conductive MnCO3@Graphene/CNT Networks for Flexible Asymmetric Supercapacitors

Abstract: The practical applications of flexible supercapacitor depend strongly on the successful fabrication of advanced electrode materials with high electrochemical performance. Herein, three-dimensional conductive network-based self-standing MnCO3@graphene/CNT hybrid film fabricated through a combination of a hydrothermal method and vacuum filtration for flexible solid-state supercapacitors is reported. The MnCO3@graphene structure is embedded in a CNT network, in which monodispersed MnCO3 nanorod is well confined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…To overcome these issues, a common strategy is followed by researchers, i.e., the addition of high electrical conductivity materials (CNTs, rGO, and bioderived carbons) to the host materials and making of composites. 24,25 Another viable alternative is defect engineering; different types of transition metal (Fe, Co, Ni, etc.) heteroatom doping/substitution in the host material could endow abundant active sites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To overcome these issues, a common strategy is followed by researchers, i.e., the addition of high electrical conductivity materials (CNTs, rGO, and bioderived carbons) to the host materials and making of composites. 24,25 Another viable alternative is defect engineering; different types of transition metal (Fe, Co, Ni, etc.) heteroatom doping/substitution in the host material could endow abundant active sites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, ordered graphitic structures of GO, rGO and pod‐like CuCo 2 S 4 /rGO can be confirmed by the Raman spectra in Figure 3b. There are two prominent peaks located at 1350 cm −1 and 1590 cm −1 for all as‐prepared samples, which are associated with the vibrations of sp 3 carbon atoms (D band) and sp 2 carbon atoms (G band), respectively [37,38] . The disorder and defect lattice concentration of graphitic carbon materials can be measured by the intensity ratio of D and G bands (I D /I G ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study 233 A good interfacial contact between electrodes and SSE can effectively improve the electrochemical performance in SSESDs. Our works suggested that the in-situ solidification of SSEs is a promising strategy to improve the interfacial contact between electrodes and SSEs and achieve the industrialization of high-performance SSESDs 237,238 .…”
Section: Design Principlementioning
confidence: 95%